Application of computer animation techniques for presenting biomechanical research results - Baca, A. (Computers in Biology and Medicine, 1998)
Computer animation is becoming a widely accepted method for presenting results of biomechanical analyses and simulations. After summarizing the main aspects of three-dimensional and video overlaid animation, two applications of these techniques are presented. A parameterized graphical model of the tennis racket has been developed, which can be used for visualizing the simulated ball-racket impact phase. In the second example, high-speed video sequences of recorded drop jumps are overlaid with graphical elements to compare methods for determining the jumping height and related parameters.These graphical elements represent quantities, which are calculated applying the different methods. Differences can vividly be demonstrated.